Perception among workers towards the misuse of power in Immigration Department, Kota Kinabalu / Emylie Alphonsus and Marylynd Sulampit - Alphonsus, Emylie; Sulampit, Marylynd (2012)
The misuse of power is critical actions that always occur in the organization whether directly or indirectly done by someone who has power. Through formal authority, cultural norms, technical expertise, and organizational politics, individuals with power attempt to influence others by a purpose to gain something. It could be for the purpose of beneficial to them as well as to the organization. The misuse of power can do in a various ways by someone who mostly have high power in the organization. In this research, the most abusing of power occur because of influence by the other who has more power, misconduct, someone that has veto power to guide the other act as well as for their personal interest. This research a researcher has use a data collection method which the questionnaire has been use to collect information that available. Other method is such instrument, sampling and sample size, unit of analysis and data analysis method where individual within employee and employer in the organization will selected and the data of analysis is known as causal study because we want to know if the factors listed are really causing the problems to be happening. Therefore, some of SPSS method has been used as to see the result on the perception on misuse of power among the employee in the public servant.